E-commerce drivers and barriers and their impact on e-customer loyalty in small and medium-sized enterprises (SMES) - Ahmad Al-Tit (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The aim of this paper is threefold: first to explore the factors that significantly and positively affect the adoption of e-commerce in SMEs; second, to determine the factors that hinder the adoption of e-commerce in these enterprises; and, finally, to investigate the impact of e-commerce-related factors on e-customer loyalty. Two samples were used for the purpose of the current study, the first of which comprised 163 managers of SMEs while the second consisted of 213 customers. Data were collected via electronic questionnaires sent to the study participants. The results identified 10 drivers of e-commerce, which are customer preferences, e-commerce perceived value, partner readiness, e-commerce cost, technical expertise, customer trust, employee knowledge and experience, top management support, perceived ease of use, and organizational culture, and 7 barriers to e-commerce adoption, which are employee technology knowledge, telecommunications, connectivity cost, technical expertise, technology cost, internet security, and legal barriers. Furthermore, the results highlighted that e-commerce ethics, information quality, customer trust, user interface quality, and customer satisfaction, respectively, are the main predictors of e-customer loyalty. Basically, organizations are called to adopt e-commerce to increase their customer loyalty. However, organizations should consider the drivers of and barriers to e-commerce adoption found in the current study.
Keywords: M30; M31; 650; drivers of e-commerce adoption; barriers to e-commerce adoption; factors affecting e-customer loyalty; SMEs